El trabajo en equipo familia- docente y el desarrollo del aprendizaje en lectoescritura de niños con necesidades educativas especiales en Educación Básica Elemental de la Unidad Educativa “María Auxiliadora” del Cantón Chunchi, año lectivo 2021-2022 - Tenezaca Quishpi, Jeny Magaly (2022)
The purpose of this research was to establish the relationship that exists between family-teacher teamwork in the development of learning in literacy of children with Special Educational Needs in Elementary Basic Education of the Educational Unit "María Auxiliadora", Cantón Chunchi, period 2021-2022. With a non-experimental design, a mixed approach and a descriptive scope, the universe of Elementary Basic General Education students of 90 students was taken as a base, of which 10 students with special educational needs were intentionally selected. Survey techniques and non-participant observation were used, as instruments a structured base questionnaire and an observation sheet. The research was carried out in the Chunchi Canton, in a Fiscomisional Educational Unit located in an urban context. This study has allowed us to conclude that there is no coordination between parents and teachers on strategies to develop literacy, since the perception is different from each other, affecting the student's literacy development, which was mainly evidenced in the LL skill. 2.3.10. Reading in a silent and personal way in situations of recreation, information and study where all the children of elementary EGB required support to achieve it.